Non-Simultaneous Blow-up Criteria for Localized Parabolic Equations (Communications in Mathematical Research, 2021)
This paper deals with blow-up solutions for parabolic equations coupledvia localized exponential sources, subject to homogeneous Dirichlet boundary conditions. The criteria are proposed to identify simultaneous and non-simultaneousblow-up solutions. The related classification for the four nonlinear parameters in themodel is optimal and complete.
Keywords: non-simultaneous blow-up; simultaneous blow-up; critical exponent.